2023
DOI: 10.1021/acsaem.2c03856
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Catalysis for the Hydrogenation of Carbon Dioxide to Methyl Formate Using a Molecular Ru–Phosphine Complex and the Metal–Organic Framework UiO-66 as Heterogeneous Acid

Abstract: The direct incorporation of CO2 into value-added base chemicals, such as methyl formate (MF), is a grand challenge to chemical science. In this work, a base-free cascade catalysis system is described to effectively convert carbon dioxide into MF. In the initial step a well-established Ru complex (i.e., RuHCl(dppm)2, dppm = 1,1-bis(diphenylphosphino)methane) is able to hydrogenate CO2 into formic acid, which subsequently undergoes a heterogeneous acid catalyzed esterification with methanol to selectively produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, Vos et al reported a combination of an organometallic Ru–phosphine complex (homogeneous catalyst) and UiO-66 metal organic framework (heterogeneous catalyst) for the conversion of CO 2 into MF at 140 °C and 6 MPa resulting in 80% MF selectivity. The Ru catalyst promoted formic acid formation while the acid sites on UiO-66 promoted methyl formate synthesis via esterification reaction Table summarizes the catalysts and reactions conditions reported in the literature for methyl formate synthesis.…”
Section: Major Products Of Thermocatalytic Liquid Phase Co2 Hydrogena...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Vos et al reported a combination of an organometallic Ru–phosphine complex (homogeneous catalyst) and UiO-66 metal organic framework (heterogeneous catalyst) for the conversion of CO 2 into MF at 140 °C and 6 MPa resulting in 80% MF selectivity. The Ru catalyst promoted formic acid formation while the acid sites on UiO-66 promoted methyl formate synthesis via esterification reaction Table summarizes the catalysts and reactions conditions reported in the literature for methyl formate synthesis.…”
Section: Major Products Of Thermocatalytic Liquid Phase Co2 Hydrogena...mentioning
confidence: 99%
“…The Ru catalyst promoted formic acid formation while the acid sites on UiO-66 promoted methyl formate synthesis via esterification reaction. 127 Table 8 summarizes the catalysts and reactions conditions reported in the literature for methyl formate synthesis.…”
mentioning
confidence: 99%
“…[24][25][26] Additionally, developing new materials and chemicals that have a lower carbon footprint, as well as recycling and reusing materials to reduce waste and emissions are important aspects towards closing the carbon loop. [27][28][29][30][31] A most viable strategy for CO 2 valorization is to use it as a building block towards value-added chemicals, [32][33][34][35][36] fuels 37,38 and construction materials. 39,40 This way, a sustainable source of chemicals and materials is provided by introducing generated CO 2 back in the production processes as an elementary building block, gradually transforming the typical linear production chain to a more sustainable production loop.…”
Section: Introductionmentioning
confidence: 99%